(untitled) - Barker, Robert J. (New Jersey, 2005)
A comprehensive study of microwave vacuum electronic devices and their current and future applications . While both vacuum and solid-state electronics continue to evolve and provide unique solutions, emerging commercial and military applications that call for higher power and higher frequencies to accommodate massive volumes of transmitted data are the natural domain of vacuum electronics technology. Modern Microwave and Millimeter-Wave Power Electronics provides systems designers, engineers, and researchers-especially those with primarily solid-state training-with a thoroughly up-to-date survey of the rich field of microwave vacuum electronic device (MVED) technology. This book familiarizes the R&D and academic communities with the capabilities and limitations of MVED and highlights the exciting scientific breakthroughs of the past decade that are dramatically increasing the compactness, efficiency, cost-effectiveness, and reliability of this entire class of devices.
Keywords: Microware devices,Millimeter wave devices,Power electronic